A systematic review of the benefits and challenges of mobile learning during the covid-19 pandemic - Saikat, S. (MDPI AG, 2021)
Following the COVID-19 outbreak, teaching and learning have been forced to move fully to the Internet rather than the conventional offline medium. As a result, the use of M-learning has risen dramatically, which was neither expected or anticipated. The challenges and benefits of such widespread usage are beginning to emerge in front of us. Thus, in this paper, we systematically review the benefits and challenges of leveraging M-learning for Science and Technology courses during the COVID-19 pandemic by educators and learners. Related articles were obtained from various databases, namely, IEEE, ACM Digital Library, ScienceDirect, and Springer. In total, 4210 related articles were initially found. Upon executing careful selection criteria, 22 articles were selected for review. After that, the advantages and threats were identified and discussed. As per our findings, it was determined that M-learning has excellent potential to be an effective platform for education provided that the identified shortcomings are resolved. This review will be helpful for education stakeholders and institutions to gauge the impact of leveraging M-learning as the only means for education to proceed. Moreover, it reveals the strengths and shortcomings that would aid in adjusting the relevant policies administered by the institutions. Furthermore, application developers will be able to comprehend the expected features that should be included in novel M-learning platforms. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.